PENGEMBANGAN KUALITAS SUSU SAPI KELOMPOK TANI TERNAK (PKTT) SIDO MAKMUR SIDOREJO, GUNUNUGPATI, KOTA SEMARANG - Lindayani; Laksmi Hartajanie; Florentinus Budi Setiawan; Shandy Jannifer Matitaputty; Elizabeth Lucky Maretha Sitinjak (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
The Sido Makmur Sidorejo Farmers' Association (PKTT), Gunungpati, Semarang City, based on dairy cow's milk, has the potential to be developed as a tourist village. However, the management of dairy products is not optimal because it is still carried out in a conventional way and less attention to hygiene and sanitation. Therefore, the quality of dairy cow's milk is part of the study. Hopefulness the results of the study can be useful for improving the quality of dairy cow's milk considering that the prospect of PKTT is very promising as a destination for tourist visits as well as to enjoy the yield of dairy cow's milk. This community service has two goals, i.e., the quality of cow's milk and the economic aspect. Analysis of milk quality is based on the quality requirements of the Indonesian National Standard (SNI) 3141.1:2111 (SNI Fresh Milk for Cows) and also focus on cleanliness of the cowshed environment and the cleanliness of the cows. While the economic aspect, business innovation is carried out based on the results of in-depth discussions and financial and economic training. Based on laboratory analysis, it is known that fresh cow's milk has several quality requirements such as particle density (1.04 g/mL), pH (6.03), fat content (4.08%) while protein content is still below quality requirements (2.37% < 2.8%). For dairy cow's milk sensory (color, flavor, taste and viscosity) there is no change. Quality requirements for microbial contamination are total plate count (≥ 1x106 CFU/mL), Staphylococcus aureus (≥ 1x102 CFU/mL), Enterobacter (≥ 1x103 CFU/mL), Escherichia coli (≥ 1x102 CFU/mL). Microbial contamination is still found due to the cleanliness of the cowshed and the cleanliness of the cows is not good. The results of discussions and training on finance and economics gave rise to business development ideas based on economic/potentials of local. So, the solution provided by the community service team was to renovate the cowshed and provide training to the Sido Makmur Sidorejo Farmers' Group (PKTT) as well as sustainable economic assistance.